The Controversy over Vivisection and Czech Women at the Turn of the 20th Century - Jastrzembská, Zdeňka (Teorie vědy / Theory of Science, 2018)
The paper presents a comparison of the character and development of the discussion on the use of animals for scientific purposes in England and the Czech Lands, with the emphasis on the connection between the anti-vivisection and women's movements. Against the background of the development of medical science, the first part describes the circumstances of the rise of the controversy and the path that led to the adoption of the first law regulating animal experiments. The second part presents the attitude of F. P. Cobbe, who was the most influential female figure in the debate. The third part maps the situation in the Czech Lands and suggests reasons as to why an organized anti-vivisection movement had not formed there. The author claims that the key role was played by the favorable perception of scientists due to their involvement in the process of National Revival. The last part presents the views on vivisection of two figures of Czech women's movement at the beginning of 20th century – P. Moudrá and E. Vozábová. The author shows that the arguments that depicted the experiment in medical science as an unnecessary and useless method of research could no longer be convincing at the time.